Tunable plasmonic enhancement of light scattering and absorption in graphene-coated subwavelength wires - Riso, Máximo (2015)
The electromagnetic response of subwavelength wires coated with a graphene monolayer illuminated by a linearly polarized plane waves is investigated. The results show that the scattering and extinction cross-sections of the coated wire can be dramatically enhanced when the incident radiation resonantly excites localized surface plasmons. The enhancements occur for p-polarized incident waves and for excitation frequencies that correspond to complex poles in the coefficients of the multipole expansion for the scattered field. By dynamically tuning the chemical potential of graphene, the spectral position of the enhancements can be chosen over a wide range.